Comparison of near-infrared (NIR) and mid-infrared (MIR) spectroscopy for the determination of nutritional and antinutritional parameters in common beans. (15th February 2020) - Carbas, Bruna; Machado, Nelson; Oppolzer, David; Ferreira, Luis; Brites, Carla; Rosa, Eduardo A.S.; Barros, Ana I.R.N.A.
Highlights: MIR and NIR have been compared for the assessment of common bean flours. The models were validated by both cross-validation (CV) and external validation. The 1st derivative of the spectral data led to the best results in both techniques. NIR was better to evaluate protein and phytic acid contents, MIR for amino acids. Abstract: Common beans ( Phaseolus vulgaris L.), represent the most consumed legume worldwide and constitute an important source of protein, being also known to contain antinutritional compounds, which compromise nutrients' bioavailability. However, the standard methodologies to assess these constituents are time-consuming and complex. Therefore, the present study evaluated the suitability of near-infrared (NIR) and mid-infrared (MIR) spectroscopies for the development of simple and reliable methods to assess protein, lipids, tannins and phytic acid contents, besides specific amino acids, in whole bean flours. Partial least squares (PLS) regression was used to develop analytical models, and external validation was performed. NIR displayed better performance for the evaluation of protein, lipids, tannins and phytic acid contents, and MIR, for the assessment of specific amino acids. In both techniques, the use of the 1st derivative was the best data treatment. Overall, both techniques represent reliable methods to evaluate the proximate and antinutritional composition of bean flours.